The Effect of Politicians' Personality on Their Media Visibility. (October 2020) - Amsalem, Eran; Zoizner, Alon; Sheafer, Tamir; Walgrave, Stefaan; Loewen, Peter John
While being frequently covered in the news media is key to political success, previous research demonstrates that some politicians are systematically more visible in the media than others. The current study advances our understanding of which politicians gain higher media visibility by exploring the effects of their personality traits. Utilizing a unique sample of 339 incumbent politicians in three countries, we find that the two personality traits that speak directly to one's interpersonal orientation—agreeableness and extraversion—affect visibility, with less agreeable and more extraverted politicians appearing more frequently in the news. We also find that open to experience and emotionally stable politicians get covered more frequently and that being highly conscientious predicts media visibility in some cases, but not in others. Politicians high on these traits, we argue, enjoy an inherent advantage in the competition for the media's attention.